If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 6d = 100 + -3d Solving 10 + 6d = 100 + -3d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '3d' to each side of the equation. 10 + 6d + 3d = 100 + -3d + 3d Combine like terms: 6d + 3d = 9d 10 + 9d = 100 + -3d + 3d Combine like terms: -3d + 3d = 0 10 + 9d = 100 + 0 10 + 9d = 100 Add '-10' to each side of the equation. 10 + -10 + 9d = 100 + -10 Combine like terms: 10 + -10 = 0 0 + 9d = 100 + -10 9d = 100 + -10 Combine like terms: 100 + -10 = 90 9d = 90 Divide each side by '9'. d = 10 Simplifying d = 10
| 9.95+0.05c=12 | | x^2+2x-41=2x+8 | | 25.99*13= | | X+5=37-7x | | 15x+732=907 | | ((4x^2)-(5xy)-(6y^2))(2x-y)= | | 9.95+0.05=12 | | -3xy^2*5x^2y^3= | | 3(4x-2)=2(5x+3) | | 8-3u=3u-8-8u | | p-3+p-7= | | 9z-8z=-7z-1+2z | | 4(-5+1)5-2(-3)3= | | 10x=5(6x+4) | | 140=6x-13 | | -35x=-4 | | y=-4x(x)-5x+3 | | 18x-3=14x-15 | | 18-5n=13 | | 1+2-x=x+5+x | | 2(x+3y)+4y= | | -12+14=-2(X+9) | | g/2.5+0.45=0.95 | | 4x+6-2x=x+9 | | 140=5x-13 | | (2x+6)+24=(2x) | | 15y+2=10y | | 3.2+14.7=-6.74 | | 150=5x-13 | | -4(-7+4x)= | | Z+1+(z-2)=(z+3)-1(z+2) | | 3x-7=9x+23 |